Is the Rotatory Knee Stability Immediately Decreased Following a Competitive Soccer Match? - Neira, Alejandro; Silvestre, Rony; Debandi, Aníbal; Darras, Daniel; Cristi-Sánchez, Iver; Barra, Ignacio; Peñailillo, Luis; De La Fuente, Carlos (Frontiers in Bioengineering and Biotechnology, 2022)
Fatigue induced by soccer-playing increased physical efforts, which might alter the transverse knee stability. Thus, we aimed to determine whether immediately following a competitive soccer match in amateur players decreases the rotatory knee stability. Secondarily, we assessed the preferred and non-preferred limb to kick a ball role in rotatory knee stability as well as the correlation between performance parameters and rotatory knee stability. We hypothesized that the knee stability immediately decreases after a competitive soccer match in amateur players. Eight healthy amateur soccer players (aged 27.2 ± 4.7 years and body mass index of 23.8 ± 1.2 kg m-2) were included immediately before and after a competitive soccer match. The rotatory knee stability was assessed in the preferred and non-preferred limbs through the acceleration and Jerk of the pivot shift maneuver and by the internal knee rotation of a pivoting landing task. Repeated-measures 2-way ANOVA for factors time and limb, and multiple comparisons were performed with α = 5%. There was a statistical significance for the main factor time in the acceleration (5.04 vs 6.90 ms-2, Δ = 1.86 ms-2, p = 0.020, ŋ2 = 0.331) and in the jerk of the pivot shift maneuver (18.46 vs 32.10 ms-2, Δ = 13.64 ms-2, p = 0.004, ŋ2= 0.456). Rotatory stability decreases following a competitive soccer match in amateur soccer players under fatigue. Both the acceleration and Jerk during the pivot shift maneuver are increased without significant internal knee rotation changes during the pivoting landing task.